2002
DOI: 10.1111/1469-8986.3920124
|View full text |Cite
|
Sign up to set email alerts
|

The temporal stability of electrodermal variables over a one‐year period in patients with recent‐onset schizophrenia and in normal subjects

Abstract: Test-retest stability of electrodermal (EDA) variables indexing both general autonomic arousal (e.g., skin conductance level, number of nonspecific skin conductance responses) and attention to external stimuli (e.g., number of skin conductance orienting responses, electrodermal responder/nonresponder status) was assessed in 71 young, recent-onset schizophrenia patients and 36 demographically matched normal subjects. Significant stability over a 1-year period was found for both patients and normal subjects for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…However, their AQ and SRS-A scores were below the cut-off scores for possible ASD and, therefore, did not require further administration of the ADOS. Also, in our study, about 21% of the ASD group and 13% of the TD group were non-responders to our habituation task, which is similar to what has been reported in earlier studies (e.g., Ikezawa et al 2012; Schell et al 2002; Schoen et al 2008). We found that the ASD non-responders showed more ASD symptoms on the ADOS than our ASD responders.…”
Section: Discussionsupporting
confidence: 91%
“…However, their AQ and SRS-A scores were below the cut-off scores for possible ASD and, therefore, did not require further administration of the ADOS. Also, in our study, about 21% of the ASD group and 13% of the TD group were non-responders to our habituation task, which is similar to what has been reported in earlier studies (e.g., Ikezawa et al 2012; Schell et al 2002; Schoen et al 2008). We found that the ASD non-responders showed more ASD symptoms on the ADOS than our ASD responders.…”
Section: Discussionsupporting
confidence: 91%
“…The ultimate source of physiological and cognitive predisposition is still to be determined (our results say little about ultimate sources), but is almost certainly a combination of genetics, early developmental experiences and more immediate environmental events. Physiological, neurological and cognitive patterns, for example, are known to be relatively stable over time [54] but hardly immutable [55]. What is suggested by our results is that for many, but certainly not all, of those individuals professing ideological convictions, their political beliefs have become biologically instantiated in a fashion that renders them sticky and slow to change-somewhere between wholly static and completely malleable.…”
Section: Discussionmentioning
confidence: 59%
“…EDA was recorded continuously throughout the dental cleaning as well as for three minutes prior to the cleaning by placing pre-gelled electrodes on the index and middle fingertips of the child's non-dominant hand. In longer-lasting situations, such as a dental cleaning, measurement of tonic skin conductance level (SCL) and frequency of non-specific skin conductance responses (NS-SCRs) are the most useful electrodermal measures (Dawson et al, 2007); these measures exhibit significant test-retest reliability (temporal stability; r ranges from .40 to .85) when measured over a duration of a few days to a year or longer (Dawson et al, 2007; Schell et al, 2002; Schoen et al, 2008). It is well-documented that these tonic EDA readings increase in stressful or painful situations (Dawson et al, 2007).…”
Section: Methodsmentioning
confidence: 99%